2009
DOI: 10.1103/physrevb.80.035115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contact and efficient charge transport in G4-DNA molecules

Abstract: We report a theoretical study highlighting the fundamental effects of contact between molecule and electrodes and of the off-diagonal disorder on the transport properties of guanine-quadruplex DNA ͑G4-DNA͒ molecules. On the basis of the effective tight-binding model which simulates charge transport through G4-DNA, the transmission coefficient and localization length are numerically calculated by using the transfermatrix method. In contrast to the physical intuition that a strong coupling at the molecule-metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…[10]- [13]. However, hole transfer experiments [14]- [20] as well as related theoretical work [21]- [25] in the chemical physics community strongly suggested that charge migration through DNA oligomers can be understood only in the context of a dynamical approach that includes the coupling of the electronic system to conformational degrees of freedom, resulting in fully or partially incoherent charge propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10]- [13]. However, hole transfer experiments [14]- [20] as well as related theoretical work [21]- [25] in the chemical physics community strongly suggested that charge migration through DNA oligomers can be understood only in the context of a dynamical approach that includes the coupling of the electronic system to conformational degrees of freedom, resulting in fully or partially incoherent charge propagation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,8,9 for recent reviews. While most of the models originally used started from a static picture of the DNA structure, 10,11,12,13 it has become meanwhile clearer that charge migration through DNA oligomers attached to electrodes may only be understood in the context of a dynamical approach. 14,15,16,17,18,19,20,21 Hole transfer experiments 22,23,24,25,26 had already hinted at the strong influence of DNA structural fluctuations in supporting or hindering charge propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [44,45] have recently shown using the Landauer theory (coherent transport) that G4-DNA exhibits much larger delocalization lengths at the band center compared to doublestranded poly(G) DNA. Surprisingly, it was also found out that the delocalization length can be even enhanced via environment-induced disorder through the backbones.…”
Section: Introductionmentioning
confidence: 99%
“…(i) The scaling between LL and PN, considering that PN embraces not only the system length, but also the number of chains, not all of them coupled to the contacts and taking part in the transmission. (ii) The quantitative agreement is not uniformly achieved along the entire energy range, particularly at the two anomalously large LL peaks, introduced by the backbones, but also present in other related systems like G4-DNA [48].…”
Section: Resultsmentioning
confidence: 90%